PENGEMBANGAN MEDIA FLASHCARD BERBASIS CERITA DONGENG “MALIN KUNDANG” BAGI SISWA SEKOLAH DASAR - Imam Fathoni; Mei Fita Asri Untari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a crucial role in improving the quality and character of students. One factor influencing successful learning is the use of appropriate media. Observations in grade IV of SDN Sawah Besar 02 Semarang showed that some students had not yet achieved the Learning Objective Achievement Criteria (KKTP) of 85%. Low learning outcomes were influenced by the lack of engaging learning media, resulting in limited student understanding of thematic material. Interviews with homeroom teachers confirmed that learning media were needed to increase student motivation and interest in learning. This study aimed to develop Flashcard media based on the fairy tale